Management of Endometriosis: An Integrative Review of National and International Guidelines - Andrade, Ana Paula Portela; Oliveira, Clara Vitória Braz Lima; Araújo, Luísa Barros Fragoso; Donald, Maria Eduarda Dantas; Portugal, Fernanda Freire Dantas; Costa, Meyrielle Santana; Andrade, Carolina Portela; Chianca, Bruna Lins; Bacha, Elizabeth (Advances in Social Sciences Research Journal, 2023)
Endometriosis is a disease characterized by the presence of endometrial tissue outside the uterus, affecting 2 to 22% of women worldwide, resulting in inferior quality of life as the condition often causes pain (dysmenorrhea, dyspareunia) and infertility. It is notable that clinical practice has changed in the last decade, with endometriosis receiving much more media attention and patients taking a more active role through different disease organizations. Considering these changes and identifying which practices are justified by medical evidence is essential. Using the descriptors: "Treatment", "Endometriosis" and "Guidelines" in the PUBMED, MEDLINE and SciELO databases, a total of 312 articles were found and, subsequently, eight articles were submitted to the selection criteria. Regarding pharmacological therapies associated with endometriosis, most of the guidelines included in this study suggest progestins, either in the form of dienogest or medroxyprogesterone acetate, and combined oral contraceptives as first-line therapy with considerable evidence. GNRH agonists and the levonorgestrel system are used as second-line treatment. Surgery also has a significant role in the treatment of endometriosis-related pain, with the excision of endometrial implants or endometriomas. Handling ovarian tissue as thoroughly as possible is recommended in order to limit the decrease in ovarian reserve. Despite very well-established guidelines, relevant diagnostic tests such as Magnetic Resonance Imaging (MRI) are inaccessible and expensive for most women, as is laparoscopic surgery, hindering the diagnosis and treatment of the disease, especially in underdeveloped countries.